Persepsi Ibu Rumah Tangga dalam Pengelolaan Ekosistem Daerah Aliran Sungai Musi Palembang - Linda Utami; Yetty Hastiana; Sri Wardhani (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
Watershed (DAS) Musi is the source of water from various economic activities,social and cultural rights of the people of Palembang. Condition of the waters of the MusiRiver Basin has declined due to natural and human activities. This study aims to determinethe relationship between the perceived level of housewives in the management of aquaticecosystems downstream watershed Musi Palembang. Data were analyzed using descriptivewith scoring based on the average value of the number of questions raised housewife. Thestudy concluded perception housewife elementary school and junior high school graduateshave poor perception while housewives graduate high school / vocational and collegegraduates have a good perception of the management of aquatic ecosystems downstreamwatershed Musi Palembang